A review of gender inequality and women’s empowerment in aquaculture using the reach-benefit-empower-transform framework approach: A case study of Nigeria - Adam, Rahma; Njogu, Lucy (Frontiers Media, 2023)
Along the aquaculture value chain, what is the status of gender equality and women’s empowerment with a particular emphasis on aquaculture? What can be done to bring about gender equality and women’s empowerment in the aquaculture sector? This article explores these questions through a systematic review of the extant literature on gender and aquaculture using Nigeria as a case study. A total of 78 articles are analyzed based on the reach-benefit-empower-transform framework. The findings show that there is gender inequality within the aquaculture value chain. In most cases, women are mainly concentrated at the nodes of the value chain, which require fewer resources to operate; furthermore, in most cases, women earn less profits compared with their male counterparts. Women’s empowerment is still at the nascent stages, while gender related transformation has yet to take root. We recommend that pro-equality gender policies in aquaculture be created and implemented. This calls for the collection and use of sex-disaggregated data and for work at the grassroots level to ensure that the manner in which women, men, boys and girls are treated and allowed to live and function in the communities they reside engenders development, harmony, gender equality and prosperity. Finally, we recommend that the reach-benefit-empower-transform framework be expanded to facilitate the evaluation of program/project-based studies.